Teachers’ basic psychological needs, (de)motivating styles and professional well-being - Huić, Aleksandra; Pavlin-Bernardić, Nina; Čižić, Nikolina (Primenjena psihologija, 2024)
In this study we adopt the lens of self-determination theory to examine the interplay between teachers’ basic psychological needs, behaviors, and well-being. We investigate teachers’ classroom behavior in the form of their (de)motivating styles as mediators between their need satisfaction/frustration and levels of their emotional exhaustion and job satisfaction. A total of 365 Croatian teachers completed an online survey filling out the Situations-in-School Questionnaire, Basic psychological need satisfaction and frustration scale, Short Index of Job Satisfaction and Emotional exhaustion scale. In line with the bright pathway, results showed that teachers with higher need satisfaction used more autonomy-supportive and structuring motivating styles and were more satisfied with their job. Teachers who used autonomy-supportive style were also more satisfied with their job, and this style partially mediated the relationship between need satisfaction and job satisfaction. In line with the dark pathway, teachers whose basic needs were more frustrated used more controlling and chaotic demotivating styles and reported higher levels of emotional exhaustion. Control and chaos as demotivating styles were not significant mediators between need frustration and emotional exhaustion, while teachers who used higher levels of the chaotic style reported lower levels of emotional exhaustion.